Legalization of Marijuana Use for Medical in Indonesia in Relation to Law Number 35 of 2009 concerning Narcotics - Saji Sonjaya (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2022)
Marijuana is one type of narcotics that is prohibited in Indonesia, as defined in Appendix I of Law Number 35 of 2009 concerning Narcotics. Marijuana is classified as a class I narcotic that cannot be used for medical purposes. Although it is illegal in Indonesia, some people use it as a medical substance to treat their illnesses. This research was conducted using the normative juridical method. According to the research findings, some Indonesians currently believe that marijuana is a dangerous plant that can cause temporary pleasure and addiction. On the other hand, there are also those who argue that cannabis can provide a sense of relaxation, pleasure, and happiness, as well as flow inspiration, drive away fatigue, boredom, even depression and stress. Another common misconception is that cannabis is a powerful medicine capable of alleviating various types of pain and slowing the spread of deadly diseases. Given that many other countries have legalized cannabis for medical purposes, the Appendix to Law Number 35 of 2009 must be revised by removing the cannabis plant, all plants of the cannabis genus, and all parts of the plant including seeds, fruit, straw, processed cannabis plants or parts of cannabis plants including cannabis and cannabis resin, and reclassifying them as class II narcotics so that they can be used as medical materials. Ganja merupakan salah satu jenis narkotika yang dilarang di Indonesia, sebagaimana didefinisikan dalam Lampran I Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika. Ganja diklasifikasikan sebagai narkotika golongan I yang tidak dapat digunakan untuk tujuan medis. Meskipun ilegal di Indonesia, beberapa orang menggunakannya sebagai bahan medis untuk mengobati penyakit mereka. Penelitian ini dilakukan dengan menggunakan metode yuridis normatif. Menurut temuan penelitian, sebagian masyarakat Indonesia saat ini percaya bahwa ganja adalah tanaman berbahaya yang dapat menyebabkan kenikmatan sementara dan kecanduan. Di sisi lain, ada juga yang berpendapat bahwa ganja dapat memberikan rasa rileks, senang, dan bahagia, serta mengalirkan inspirasi, mengusir penat, bosan, bahkan depresi dan stres. Kesalahpahaman umum lainnya adalah bahwa ganja adalah obat yang ampuh yang mampu meringankan berbagai jenis rasa sakit dan memperlambat penyebaran penyakit mematikan. Mengingat banyak negara lain yang telah melegalkan ganja untuk kepentingan medis, maka Lampiran Undang-Undang Nomor 35 Tahun 2009 harus direvisi dengan menghapus tanaman ganja, semua tanaman genus ganja, dan semua bagian tanaman termasuk biji, buah, jerami, tanaman ganja yang telah diolah atau bagian tanaman ganja termasuk resin ganja dan ganja, serta mengklasifikasikannya kembali sebagai narkotika golongan II agar dapat digunakan sebagai bahan medis.